POLA KONSUMSI ORANG DENGAN HIV/AIDS (ODHA) PEREMPUAN KE LOMPOK DUKUNGAN SEBAYA NUSA TENGGARA BARAT - Retno Mardhiati (UHAMKA PRESS, 2016)
ABSTRACTWomen living with HIV infected from their husband are more experiencing decline inconfdence and quality of live. This confdence inﬂuences the food consumption patterns. Thiss a descriptive research with quantitative data using cross sectional design. The data werecollected by interviewing women living with HIV using questionnaire in 2012. The populationn this study is the whole member of West Nusa Tenggara peer support group, totaling 25person. The sample is the total population using saturated sampling technique. The result shows that most of women living with HIV are having food consumption frequency three times(72%), and snack consumption frequency twice (40%). Most women living with HIV statedthat they rarely consume vegetable everyday (40%) and rarely consume fruits everyday (84%).and most women living with HIV never consume packed food (68%) and rarely consume fastfood (60%). Milk consumption habit of women living with HIV is very rare, only 4% of therespondents who stated always consuming milk. Sweet tea drinking is also rarely done (60%)and most of the respondents don’t consume coffee (56%). The proportion of the respondentswho stated consuming packed drink often is 8%. Herbal medicine and supplement are stillrarely consumed, and most of the respondents stated that they never consume supplement(44%) and herbal medicine (80%). Nutrition education approach effort is an important to do towomen living with HIV through peer support group.